URGENSI ANALISIS PEKERJAAN DALAM MANAJEMEN SUMBER DAYA MANUSIA ORGANISASI - Mohamad Muspawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Job analysis is an important part of human resource management activities. Because one that delivers the success of an organization is the extent to which the organization's completeness analyzes the work that is imposed on all of the human resources it has. Job analysis is a systematic activity in examining a job by determining the tasks, obligations and responsibilities of a job, knowledge, capability and expertise needed to perform work within an organization. The process of analyzing the work through the steps as follows: 1) Determine the use of job information analysis results; 2) Gather background information; 3) Selecting mukawal positions to be analyzed work; 4) Gathering job analysis information; 5) Review information with interested parties; 6) Develop job descriptions and job specifications and 7) Take into account the development of the company / organization.Keywords:  Urgen, Job Analysis, Organization.